2020
DOI: 10.37908/mkutbd.737231
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between bodyweight and morphological traits in Sahelian goats of Nigeria using path analysis

Abstract: A total of 163 Sahelian goats of both sexes (64 males and 99 females) were randomly sampled and used in this study to assess the relationship between bodyweight and morphological traits using multivariate path analysis method. Methods: Data were obtained on bodyweight (kg), height at withers (HW), body length (BL), paunch girth (PG) and heart girth (HG). Means (+SD and CV) and correlation coefficients between bodyweight and morphological parameters were also evaluated using the statistical procedures of SPSS 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…The current correlation results further indicated highly statistical correlation between body weight and morphometric traits (Heart girth and body length). The results were in line with the results of other studies ([17]; [5]; [13]) who indicated a highly statistical correlation between body weight, heart girth and body length. The results means that by improving heart girth, body volume and body length will improve body weight of the Savanna goats.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current correlation results further indicated highly statistical correlation between body weight and morphometric traits (Heart girth and body length). The results were in line with the results of other studies ([17]; [5]; [13]) who indicated a highly statistical correlation between body weight, heart girth and body length. The results means that by improving heart girth, body volume and body length will improve body weight of the Savanna goats.…”
Section: Discussionsupporting
confidence: 92%
“…They are crucial to the livelihood of the rural farmers since they supply them with meat, milk, hides, manure and source of income [4]. Body weight is very important trait since it can direct farmers to run proper management practices in their herd and it can also be used check the development of livestock [5]. However, measuring body weight of goats is not easy at a rural level due to lack of weighing scales [6].…”
Section: Introductionmentioning
confidence: 99%
“…(2015) on path analysis for body measurements on weaning weight of Saanen kids, contrary may be due to use of different breed. Additionally, previous studies put forward path analysis as a useful technique in determining WW using biometric traits in animal breeding in goats (Rotımı et al 2020), in cattle (Tyasi et al 2020), in chickens (Egena et al 2014;Tyasi et al 2018), in pigs (Al Ard Khanji et al 2018 and ducks (Yakubu et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Live body is a crucial trait in animal husbandry as it determines animal management practices like feeding and drug dosage (Rotimi et al, 2020). One of the ways to estimate live body weight of sheep is the use of independent linear body measurements to develop prediction models.…”
Section: Phenotypic Correlations Between Live Body Weight and Linear ...mentioning
confidence: 99%
“…Live body weight of animals in many parts of the world play a critical role as the most important economic trait that in uences the farmers' daily decision-making regarding animal management practices (Rotimi et al, 2020). Live body weight is used in assessment of responses of animals to different diets, in monitoring growth rate and in determining growth traits (Hlokoe et al, 2022).…”
Section: Introductionmentioning
confidence: 99%